Persepsi Penyuluh Pertanian Lapang tentang Perannya dalam Penyuluhan Pertanian Padi di Provinsi Banten - Narso, Narso; Saleh, Amiruddin; Asngari, Pang S; Muljono, Pudji (Jurnal Penyuluhan, 2015)
This research aim are: (1) To study perception of agriculture extension agent about their role in agriculture activity in Banten, ( 2) To explain of factors which have correlation with the perception of agriculture extension agents about their roles in agriculture extension activity in Banten, (3) To analysing degree of factors which have correlation with the perception of agriculture extension agents about their roles in agriculture extension activity in Banten. Research was designed with the method survey the deskriptive-korelasional. Analyse the data used the descriptive statistic and statistical analysis inferensial. For the statistic of descriptive use the frequency, percentage, mean score, total mean score and tabulation traverse, analysis of statistic inferensial used to see the relation the dependen variable with the independen variable by rank Spearman. Factors which correlate with the perception are (1) characteristic of extension agent consisted by the age, formal education, and experience; (2) physical Environment consisted by the institute, mean the work, construction and supervise, and career development; (3) social economics environment: Environment of work, partner opportunity, and access to economic resources; and (4) Motivation: achievement motivation, affiliate motivation, and power motivation. Key word: Perception, Role, agriculture extension agent